Cone beam computed tomography findings in monostotic fibrous dysplasia of the mandible: a case report - Restiti, Rr Dinar; Budhiana, Aries Sugih; Pramanik, Farina (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2025)
Objectives: This case report aims to describe the three-dimensional radiographic characteristics of fibrous dysplasia affecting the mandible. Case Report: A 38-year-old female patient presented to the Dental Hospital of Padjadjaran University with complaints of swelling in the right lower jaw, accompanied by a sensation of heat and limited mouth opening of approximately 2 cm. The patient was subsequently referred for a Cone-Beam Computed Tomography (CBCT) examination. Conclusion: Based on the CBCT findings, radiographic features revealed radiolucent, ill-defined, and expansile lesions involving the facial bones. These findings support a radiological diagnosis suggestive of fibrous dysplasia.